RELEVANSI KHI DAN FIQH SYAFI’IYYAH DALAM PRAKTEK UPAYA PENCEGAHAN SAKSI FASIQ DI DESA KARANGSEMI - Rohim Arrozy, M. Fathur; Zahro, Ahmad (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
Witness marital status with legally disabled witnesses from the perspective of KHI and Fiqh Syafi'iyyah Case studies in Karangsemi Belin Gondang Village, Nganjuk Regency. The focus of legal defects here is the unfairness of a witness in marriage or commonly called a wicked witness, seeing that the presence of fair witnesses is a requirement of a witness in marriage. This study used a qualitative method and the primary data collection method was observation, interviews and documentation of the Karangsemi community component and reading the classical literature of Syafi'iyyah scholars. Fiqh Shafi'iyyah. This research results in the first, KHI does not explain in detail regarding efforts to prevent witnesses who are legally disabled or wicked, while Fiqh Syafi'iyyah recommends efforts to prevent legal defects by repentance. Second, there are two efforts made by Karangsemi residents, namely by sorting and choosing witnesses carefully based on dhohir and usually and carrying out rituals before the contract by reading Istigfar, Sholawat, Syahadataini as a form of repentance. Third, the prevention efforts presented by Karangsemi residents are relevant to the KHI and Fiqh Syafi'iyyah perspectives.marriage is the core thing in the marriage ceremony, often ordinary people present witnesses without knowing the criteria for a valid witness. This research reviews efforts to prevent